Translating Elements of Culture Using the Example of the Series “Only Fools and Horses” - Križanec, Klaudia; Palašić, Nikolina (Corpora in Language Learning, Translation and Research: Proceedings of the International Conference Corpora in Language Learning, Translation and Research held at the University of Zadar (August 23–24, 2023), 2025)
Since language expresses, embodies, and symbolizes cultural reality, difficulties will inevitably occur during translation when transferring culturally marked expressions from one language to another. Through translation, other cultural realities are introduced into the target text, which, over time, inevitably alter the target language as well. The issue of how to translate cultural elements has been addressed by numerous authors, so in the introduction of this paper, we describe and compare some of them and decide to apply Pedersen’s taxonomy to the corpus (Pedersen 2011). For the analysis of cultural elements and translation strategies, the series Only Fools and Horses was chosen because it is deeply rooted in the culture of the English working class and abounds in culturally specific elements, for which the Croatian translator found some interesting solutions. Twenty episodes were randomly selected for analysis, and each analyzed section of the text is accompanied by the corresponding episode and the timestamp in minutes and seconds indicating when the selected subtitle appeared on the screen.